National Association of Medical Examiners Position Paper: Medical Examiner, Coroner, and Forensic Pathologist Independence. Issue 1 (March 2013) - Melinek, Judy; Thomas, Lindsey C.; Oliver, William R.; Schmunk, Gregory A.; Weedn, Victor W.; ,
Objective: Forensic pathologists play a vital role in the justice system in matters concerning questions of death. Science as applied in the justice system should be objective and neutral. Since the goals of medical examiners and coroners are to determine the cause and manner of death for certification and public health functions (goals different and distinct from the missions of law enforcement agencies), it is important that medicolegal death investigation be independent. Accurate investigation, examination, reporting, and testimony by forensic pathologists are important to determine the cause and manner of death of individuals who die under sudden, unexpected, or violent circumstances. These cases can become the focus of political or legal pressure by individuals or offices seeking to influence the pathologist's findings. This pressure, even if seemingly unsuccessful in an individual case, can introduce error, bias, and corruption into the medicolegal investigation process. This paper reinforces the principle that medical examiners, coroners and forensic pathologists should be allowed to perform medicolegal investigations free of these influences. Participants: The ad hoc Committee on Medical Examiner Independence of the National Association of Medical Examiners (NAME), a self-selected volunteer committee, developed this position paper. The findings are based on surveys of the NAME membership regarding members' experience with, and reaction to, outside influence. Evidence: Surveys of NAME members revealed that medical examiner independence was important to most members. Over 70% of survey respondents had been subjected to pressures to influence their findings, and many had suffered negative consequences for resisting those influences. In a separate study, over 30% of respondents indicated that fear of litigation affected their diagnostic decision-making. In 2009, the National Research Council of the National Academies published recommendations to strengthen the forensic sciences; they specifically recommended that medical examiner and coroner offices should be independent from law enforcement agencies and prosecutors' offices. Consensus Process: This position paper represents the consensus of the ad hoc Committee on Medical Examiner Independence, submitted to the Executive Committee and Board of Directors of NAME, and subject to comment and review by the membership. Conclusions: It is the position of NAME that forensic pathologists working in or for medical examiner or coroner offices or as private consultants should be permitted to objectively pursue and report the facts and their opinions of those cases which they are investigating independent of political influences from other agencies within their respective jurisdictions and independent of the threat of litigation.